Gemini G.E.L. : Recent Prints and Sculpture - Ritchie, Charles; Fine, Ruth E. (Washington : National Gallery of Art, 1994)
Murray, Elizabeth ; Rothenberg, Susan ; Celmins, Vija ; Steinberg, Saul ; Baldessari, John ; Flavin, Dan ; di Suvero, Mark ; Price, Kenneth ; Diebenkorn, Richard ; Kelly, Ellsworth ; Francis, Sam ; etc.
Gemini G.E.L. : Recent Prints and Sculpture, National Gallery of Art, Washington, June 5 - October 2, 1994
boek